Automatic Control of Bottle Contents and Separation of Empty Bottles in Packaging Process Using Programmable Logic Controller Siemens S7-1200 - Imnadir, Imnadir; Junaidi, Abdul Khair; Arief, Dodi Sofyan; Dalil, M (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2024)
Filling liquid into bottles with the same volume is an important part of product packaging. All packaged bottles must be filled per a product's provisions. A device is needed to control the contents of the bottles from a certain distance or from outside the bottles by moving on the conveyor track. So that the bottles can be automatically filling the same volume continues to the packaging process. To be able to control the contents of the bottle automatically and properly may need a tool and a control program. This research was carried out to be able to control the contents of transparent bottles, using a Siemens S7-1200 PLC, so that a system for controlling bottle contents quickly and precisely, which helps the production process run smoothly. The main components used in this research were the Siemens S7-1200 Programmable Logic Controller, Omron E3S-DB sensor, and pneumatic cylinder. The result showed the Control Module Program 1 successfully detected empty bottles and rejected them properly. Control module program 2 successfully moves the pneumatic cylinder to move the cylinder continuously until the stop button was pressed. The module 3 programs succeeded in moving the cylinder, which was limited to only 10 repeated movements until it stopped.